The iron-entry pores in Dps-like proteins as a potential drug-design targe: Structural investigations - Tatsis, Polychronis (My University, 2022)
Streptococcus suis is an emerging catalase-negative zoonotic pathogen that uses the peroxide resistance protein (Dpr) as a defensive mechanism against oxidative stress. Dpr belongs to a family of proteins that form spherical dodecamers with a hollow cavity in the middle. Dpr, as other members of the family, uses four pores found on the surface of the dodecamer and formed by the N-terminals of adjacent monomers (N-terminal pores) to take up Fe2+ and deposit it inside the cavity after its oxidation to Fe3+ in ferroxidase sites in the interior of the dodecamer. In this way, the generation of toxic hydroxyl radicals via Fenton’s reaction is avoided. In this study, a new purification process and crystallization conditions for Dpr were found. Besides, the ligandability of Dpr for use as a drug target was investigated. 6xHis-tagged Dpr was successfully produced and purified. Crystallization screens yielded crystals in 10 conditions and further optimization led to crystals suitable for structural analysis. Synchrotron X-ray data were collected to 2.2 Å resolution. A novel ligand library design led to an initial library of 82 compounds that could act as possible N-terminal pore blockers. After a score threshold of -7, twenty (20) ligands remained. Similar, to the latter ones, marketed ligands were retrieved, and ten (10) of them were kept, all sharing the feature of having aromatic rings. Phe133 was found as the only residue responsible for Pi-pi interactions with the ligands. This is the first successful approach for 6xHis-tag Dpr crystal production and structure determination. It is also the first approach for ligand creation against the N-terminal pores of the Dpr, setting the basis for new possible future therapeutic approaches for S. suis-related infections treatment, avoiding the obstacle of antibiotic resistance.
Keywords: oxidative stress, DNA-binding protein, antibiotic resistance, drug design, Streptococcus suis, meningitis, ferroxidase, crystallization